Chronic ethanol exposure increases goosecoid (GSC) expression in human embryonic carcinoma cell differentiation. Issue 1 (4th February 2013) - Halder, Debasish; Park, Ji Hyun; Choi, Mi Ran; Chai, Jin Choul; Lee, Young Seek; Mandal, Chanchal; Jung, Kyoung Hwa; Chai, Young Gyu
ABSTRACT: Fetal alcohol spectrum disorder (FASD) is a set of developmental malformations caused by excess alcohol consumption during pregnancy. Using an in vitro system, we examined the role that chronic ethanol (EtOH) exposure plays in gene expression changes during the early stage of embryonic differentiation. We demonstrated that EtOH affected the cell morphology, cell cycle progression and also delayed the down‐regulation of OCT4 and NANOG during differentiation. Gene expression profiling and pathway analysis demonstrated that EtOH deregulates many genes and pathways that are involved in early embryogenesis. Follow‐up analyzes revealed that EtOH exposure to embryoid bodies (EBs) induced the expression of an organizer‐specific gene, goosecoid (GSC), in comparison to controls. Moreover, EtOH treatment altered several important genes that are involved in embryonic structure formation, nervous system development, and placental and embryonic vascularization, which are all common processes that FASD can disrupt. Specifically, EtOH treatment let to a reduction in ALDOC, ENO2 and CDH1 expression, whereas EtOH treatment induced the expression of PTCH1, EGLN1, VEGFA and DEC2 in treated EBs. We also found that folic acid (FA) treatment was able to correct the expression of the majority of genes deregulated by EtOH exposure during early embryo development. Finally, the present study identified a gene set including GSC, which was deregulated by EtOH exposure that may contribute to the etiology of fetal alcohol syndrome (FAS). We also reported that EtOH‐induced GSC expression is mediated by Nodal signaling, which may provide a new avenue for analyzing the molecular mechanisms behind EtOH teratogenicity in FASD individuals. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In the present study, we examined the role that chronic ethanol (EtOH) exposure plays in gene expression changes during early stage of embryonic differentiation. By employing a transcriptomic approach, we have identified genes, including GSC, which are vulnerable to EtOH exposure during the early stages of embryonic development. We reported that EtOH deregulates GSC expression by altering nodal signaling pathway, which may provide a new avenue for analyzing the molecular mechanisms behind EtOH teratogenicity in FASD individuals.